(untitled) (Faridpur Medical College Journal, 2011)
Silicosis is not an uncommon disease in Bangladesh as a good number of people are exposed to silica dust in their working places. Again pulmonary tuberculosis is also common here, the risk of which is increased by about 30 folds in silicosis. In the reported case, a young stone cutter of 40 years was admitted to Faridpur Medical College Hospital with progressive dyspnoea, dry cough and radiological appearance of multiple small and a large nodular pulmonary mass. Two of his brothers, also stonecutter, died of similar disease. In this context the patient was diagnosed as a case of chronic complicated silicosis and treated symptomatically as there is no curative treatment. A good number of people are engaged in stone cutting in our country including Faridpur district and are vulnerable to this progressive and non-curable disease. To aim of this case report is to make those people to be aware about the condition, so that they can protect themselves by taking appropriate measures (i.e. using protective mask) and should monitored their condition by regular chest x-ray. If early signs of silicosis is detected the worker should changed their job. DOI: 10.3329/fmcj.v5i2.6827 Faridpur Med. Coll. J. 2010;5(2):69-71